2001
DOI: 10.1021/es001466k
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Characterization of Fine Particle Emissions from Fireplace Combustion of Woods Grown in the Northeastern United States

Abstract: A series of source tests was conducted to determine the chemical composition of fine particle emissions from the fireplace combustion of six species of woods grown in the northeastern United States: red maple, northern red oak, paper birch, eastern white pine, eastern hemlock, and balsam fir. Results include fine particle emission rates for total mass, organic and elemental carbon, ionic species, elemental species including potassium, and over 250 specific organic compounds. The data are intended for use in so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

41
410
5
6

Year Published

2002
2002
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 567 publications
(462 citation statements)
references
References 42 publications
41
410
5
6
Order By: Relevance
“…The emissions from the combustion of maritime pine whether in the woodstove or in the fireplace were the lowest among all biomass fuels. Fine et al (2001Fine et al ( , 2002Fine et al ( , 2004b obtained PM 2.5 emission factors for the fireplace and woodstove combustion of American tree species lower than those observed in this study; the PM 2.5 emission factors were in the range 0.88e3.4 g kg À1 of wood burned (as fired) in a woodstove, and between 1.6 and 11.4 g kg À1 of wood burned (as fired) in the fireplace. As stated in the literature, particle emission factors from residential biomass combustion may show wide variation due to the type of fuel, the characteristics of combustion facility, dilution techniques used, sampling procedures, burning rate and the moisture content of the fuel (Fine et al, 2004b;Kowalczk et al, 1981;Lipsky and Robinson, 2005;Wardoyo et al, 2006).…”
Section: Resultscontrasting
confidence: 68%
See 2 more Smart Citations
“…The emissions from the combustion of maritime pine whether in the woodstove or in the fireplace were the lowest among all biomass fuels. Fine et al (2001Fine et al ( , 2002Fine et al ( , 2004b obtained PM 2.5 emission factors for the fireplace and woodstove combustion of American tree species lower than those observed in this study; the PM 2.5 emission factors were in the range 0.88e3.4 g kg À1 of wood burned (as fired) in a woodstove, and between 1.6 and 11.4 g kg À1 of wood burned (as fired) in the fireplace. As stated in the literature, particle emission factors from residential biomass combustion may show wide variation due to the type of fuel, the characteristics of combustion facility, dilution techniques used, sampling procedures, burning rate and the moisture content of the fuel (Fine et al, 2004b;Kowalczk et al, 1981;Lipsky and Robinson, 2005;Wardoyo et al, 2006).…”
Section: Resultscontrasting
confidence: 68%
“…2). The carbon content of particle emissions from the combustion of Portuguese woods was compared with that determined by Fine et al (2001Fine et al ( , 2002Fine et al ( , 2004b and by Gonçalves et al (2010) in Table 2. The OC values obtained by Fine et al (2002) for the fireplace combustion of selected American wood species are about two times higher than those obtained in our study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One reason could be levoglucosan's scarcity in its natural form [1][2][3][4]. However, because of the serious problem of limitations of fossil fuel reserves, studies on the degradation of cellulose to be singular sugar such as glucose or levogluocsan have been given much attention, as glucose or levoglucosan derived from cellulose can be easily fermented into alcohol or other useful products.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Schauer et al [1] found that levoglucosan was the major constituent in the fine particulate emissions from residential fireplace combustion of wood, contributing 18-30% of the fine particulate organic compound emissions. Since fine particulate matter emitted during wood combustion was known to contribute a significant fraction of the total fine aerosol concentration in the atmosphere of both urban and rural areas [2], levoglucosan was selected to be a good candidate as a molecular tracer for wood combustion in source-apportionment studies [3]. Guillen et al [4] also found that levoglucosan was the main component of the residues obtained from evaporation at room temperature of the remaining aqueous phase after extraction of commercial smoke flavorings with dichloromethane.…”
mentioning
confidence: 99%